Influence of the Stimulant Humimax on the Productivity of Repeat Sunflower Crops (Texas Journal of Agriculture and Biological Sciences, 2023)
In the conditions of the Republic, especially in the southern regions, it is possible to sow cotton, sunflower, rice, potatoes, vegetables of melons, legumes, corn, and other crops as repeat crops after winter wheat, and also get two harvests a year. However, as a result of global climate change due to unfavorable climate, water scarcity, and drought in recent years, problems have been created in obtaining a high and high-quality harvest from repeated crops sown after winter wheat. To solve these problems, it is considered relevant to develop and scientifically substantiate optimal norms and terms for the use of growth stimulants in the cultivation of sunflower sown as a repeat crop after winter wheat. In agriculture, the use of plant growth stimulants is justified by their high efficiency and effectiveness. Stimulants shorten the growing season and also help to correct the condition of crops, due to unfavorable environmental conditions, the treatment of crops with growth stimulants has a positive effect on the growth and development of plants. In the conditions of bald Meadow soils of the Surkhandarya region in the southern zone of the Republic of Uzbekistan, the use of optimal timing and doses of the growth stimulator Gumimax for obtaining a highquality crop of repeated sunflower crops of the Jakhongir variety was studied. The use of the Gumimax stimulator on repeated sunflower culture before sowing seeds with a norm of 0.75 l t-1 and in the phase of the appearance of 3-4 leaves with a norm of 0.4 l ha-1 , a seed yield of 1,97 t ha-1 was obtained, and oil content of 48.6%, grain yield increased by 0,35 t ha-1 , the oil content was higher by 3.1%.